Reduction of potassium fixation by 2 humic-acid fractions in vermiculitic soils - Olk, D.C.; Cassman, K.G. (Wiley, 1995)
The capacity of soil organic matter (SOM) to reduce K fixation was investigated in calcareous vermiculitic soils. Humic acid fractions were extracted with the use of a modification of the standard NaOH extraction procedure. The mobile humic acid pool (MHA) was extracted without initial decalcification. Addition of MHA to the vermiculitic soils reduced K fixation and resulted in greater total extractable K and highly labile K, as well as greater plant K uptake. The Ca humate pool (CaHA) was extracted after decalcification, and it had little effect on K availability. An increase in extractable and highly labile K occurred within 4 h of MHA addition and thus appears to result from a rapid exchange reaction and not from mineral dissolution; the latter was confirmed in separate experiments with organic acids. This rapid effect could be reproduced by addition of dodecylammonium chloride. We speculate that the enriched amino acid content and increased solubility of MHA, compared with the more humified CaHA, contribute to the greater influence of MHA on K equilibria. The less soluble, more condensed CaHA is more likely to precipitate with Ca2+. The capacity of solubilized MHA to hold K+ against soil adsorption was also apparent when soil was separated from MHA by a dialysis membrane. These results provide further evidence that young N‐rich SOM fractions such as MHA play an important role in governing K availability in soils with high K fixation potential.